Genetic Variation in the β2-Adrenergic Receptor: Impact on Intermediate Cardiovascular Phenotypes - Hesse, C.; Eisenach, J. H. (Current Pharmacogenomics and Personalized Medicine, 2008)
Genetic variation in drug targets (e.g. receptors) can have pronounced effects on clinical responses to endogenous and exogenous agonists. Polymorphisms in the gene encoding the β2-adrenergic receptor (β2-AR) have been associated with altered expression, down-regulation, and altered cell signaling in vitro. Because β2-ARs play a crucial role in the regulation of the cardiovascular system, the functional importance of genetic variation in the β2-AR on cardiovascular responses to physiological or pharmacological stimuli has gained widespread attention. The objective of this review is to characterize these intermediate cardiovascular phenotypes and their influence on cardiovascular disease and adrenergic drug responses. Two common single nucleotide polymorphisms, encoded at codon 46 (Gly16Arg) and 79 (Gln27Glu) of the β2-AR gene, have been studied intensively. They have been shown to be associated with altered vasodilator responses to regional and systemic administration of β2-agonists, altered cardiovascular responses to sympathoexcitatory maneuvers, and altered myocardial function. Importantly, these intermediate physiological patterns may influence the development of and the outcomes associated with hypertension and other cardiovascular diseases. As recently reported, β2-AR gene variation can risk-stratify patients receiving β-blocker therapy and may predict β-blocker efficacy in patients post acute coronary syndrome or in patients with heart failure. Further studies will advance our understanding of the link between β2-AR genotypes, intermediate cardiovascular phenotypes, and clinical phenotypes. In the long term, reassessment of the benefits of β-blocker-therapy within genotype groups should be carried out with the ultimate goal to design the optimal therapeutic regimen for the individual patient.
Keywords: genotype